The Analysis of Seventh-Grade Students’ Reading Skill through the Implementation of Cooperative Learning Method - Amalyasari, Maya Rizki; Ate, Debora Wunga (UIBU, 2023)
Reading skills are very important for all circles, groups, and levels of education. Starting from junior high school activities, students must master reading maximally and optimally. Student skills must be nurtured and developed, and students must be skilled in Reading and master reading fluently. The researcher used qualitative descriptive research. The data collection techniques that researcher used were observation, questionnaires, student scores, and documentation. This research was conducted at SMP Bakti Luhur and the subject was 20 students of SMP Bakti Luhur. The purpose of this study was to know the difficulties found by students in reading. Based on the result of observations, researcher found three difficulties in reading, namely problems in pronunciation of words, difficulty reading many words, and difficulty reading long sentences. Result of the students’ opinions related to use cooperative learning method, the researcher can conclude that most students liked learning reading by using the cooperative learning method, this method also improved the student’s ability to read English texts. The results of scoring students on the use of cooperative learning methods showed that cooperative learning methods can improve students' reading skills and made students learn to read English texts more easily.